Transmission Electron Microscopy Characterization of Nanomaterials - Kumar, Challa S.S.R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Third volume of a 40volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Transmission electron microscopy characterization of nanomaterials. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.
TEM Characterization of Biological and Inorganic Nanocomposites -- Electron Microscopy of Thin Film Inorganic and Organic Photovoltaic Materials -- TEM for Characterization of Semiconductor Nanomaterials -- Study of Polymeric Nano-Composites by 3D-TEM and Related Techniques.-TEM for Characterization of Nanowires and Nanorods -- TEM for Characterization of Core-Shell Nanomaterials -- Valence Electron Spectroscopy by Transmission Electron Microscopy -- TEM Characterization of Nanocomposite Materials -- High Resolution in STEM Mode: Individual Atom Analysis in Semiconductor Nanowires -- Electron Microscopy for Characterization of Thermoelectric Nanomaterials -- TEM for Characterization of Nanocomposites Oxide Thin Films: A Case Study on Solution-Derived Lanthanum Strontium Manganites -- TEM Characterization of Metallic Nanocatalysts -- 3D Electron Microscopy Applied to Nanoscience.-Transmission Electron Microscopy of 1D-Nanostructures.
Keywords: Chemistry; Nanochemistry; Materials; Chemistry; Chemistry/Food Science, general; Materials Science, general; Nanochemistry; Nanoscale Science and Technology